Effect of human serum albumin on clinical outcomes in pediatric patients undergoing gastrointestinal surgery - Ping Li; Mi Zhou; Da-Yu Chen; Ya-Kun Liu; Feng Liu; Yong-Gen Xu; Jian Wang; Huan Gui (Frontiers in Pediatrics)
PurposeThis study aims to evaluate the effectiveness of administering 20% human serum albumin (HSA) on short-term clinical outcomes in pediatric patients undergoing enteric anastomosis, with a specific focus on postoperative hospital stay (PHS), postoperative fasting duration (PFD), and the incidence of postoperative complications (PCs).MethodsThis was a single-center, retrospective cohort study. Patients aged between 1 month and 18 years who underwent simple intestinal anastomosis were included. Comprehensive data, including patient demographics, prescribed medications, laboratory test results, and surgical records, were meticulously extracted from electronic patient dossiers. The primary endpoint was PHS. The second endpoint included PFD and PCs. Since this was a retrospective cohort study, we used propensity score matching (PSM) to balance different variables. The efficacy of 20% HSA on clinical outcomes was assessed by univariate and multivariate logistic regression analyses.ResultsAmong a cohort of 242 patients, 67 (27.69%) were administered 20% HSA for over 2 days during the early postoperative stage. A dose-related pattern of HSA efficacy on clinical outcomes was observed in the PSM cohort. After adjustment, HSA overuse was identified as an independent risk factor for prolonged PHS and a higher complication incidence, with odds ratios of 6.56 [95% confidence interval (CI): 2.12–20.32] and 5.14 (95% CI: 1.21–21.83), respectively.ConclusionsOveruse of 20% HSA in the early postoperative stage does not contribute to improved clinical outcomes in pediatric patients undergoing gastrointestinal surgery.